Limitations on ownership. On private limitations: Can the registry court legislate? - Ortiz Pasco, Jorge (2024)
The article develops the variety of restrictions to the right to property in Peru, many of them overlooked, but very necessary to know. In this task, the author also takes a position on the controversial restriction on the transfer and encumbrance of property by agreement between private parties.Some limitations have been pronounced by the highest administrative registry instance: the Registry Court; the author questions its legislative power through an analysis of the changes brought about by the plenary sessions LXII, XCIV and XCIX, in addition to the pronouncements of the Constitutional Court and the provisions of the Civil Code of 40 years of validity.